Using the Kahoot Game-Based Learning Platform in a University Environment - Masouras, Panicos; Avgousti, Sotiris (My University, 2021)
Due to the limitations inherent in traditional learning management systems as regards the assessment options, educators are faced with the challenge to either invent and improvise new ways of engaging students based on their experiences and expertise or rely on the exploitation of software tools that have been proliferating for this purpose. The authors preferred the latter approach and used Kahoot, a game based learning platform to engage their students in a second year class of 58 students of a nursing department at a University in Cyprus. The results of this experience will be presented highlighting the increased degree of satisfaction amongst students for enhancing their learning and motivating them to take up assessment tasks for achieving better academic results.
Keywords: Kahoot; Game based learning; Assessment; Student engagement; Nursing